The formulation of halal market concept in Indonesia - Marcellina, Aaliya; Arsyianti, Laily Dwi (Halal Studies and Society, 2025)
This study aims to conceptualize halal traditional markets (Pasar Rakyat) in Indonesia as multidimensional socioeconomic systems grounded in Islamic principles. Although halal industry has experienced growth in sectors, such as food, pharmaceuticals, and cosmetics, the governance framework for public markets remains underdeveloped. Using a qualitative exploratory approach, this current study analyzed 54 academic articles published between 2015 and 2025 through thematic coding using NVivo 15 Plus software. The results showed that there were 5 dominant thematic domains centered around the keywords of halal, market, products, Muslim, and Islam, reflecting the intersection of religious values, consumer behavior, institutional regulation, and socio-cultural identity. These indicated that halal market extended beyond product compliance to include ethical transactions, institutional regulations, and cultural representation. Traditional markets, particularly in Indonesia, played a significant role in the daily lives of Muslim communities but were often overlooked in halal development strategies. This study contributes to academic and policy discourse by proposing a more integrated and contextual understanding of halal market that is consistent with religious values and modern economic demands. However, the scope is limited to secondary data and literature analysis, which may not fully capture practical challenges in the field. Future studies are advised to include empirical investigation and stakeholder perspectives to strengthen these insights.